Managerial Reactions to Employee Dissent: The Impact of Grievance Activity on Performance Rating - Klaas, Brian S.; DeNisi, Angelo S. (Academy of Management Journal, 1989)
This study explored whether managerial reactions to grievance activity introduced bias into the process of performance appraisal. Using panel data techniques and data on unionized employees in a public sector organization, we examined the relative impacts of grievances filed against supervisors and against organizational policy. The pattern of results obtained suggests that the relationship between grievance activity and performance ratings is due at least in part to bias triggered by employees' filing and winning grievances against supervisors.